A gecko skin micro/nano structure – A low adhesion, superhydrophobic, anti-wetting, self-cleaning, biocompatible, antibacterial surface. (15th July 2015) - Watson, Gregory S.; Green, David W.; Schwarzkopf, Lin; Li, Xin; Cribb, Bronwen W.; Myhra, Sverre; Watson, Jolanta A.
Graphical abstract: Abstract: Geckos, and specifically their feet, have attracted significant attention in recent times with the focus centred around their remarkable adhesional properties. Little attention however has been dedicated to the other remaining regions of the lizard body. In this paper we present preliminary investigations into a number of notable interfacial properties of the gecko skin focusing on solid and aqueous interactions. We show that the skin of the box-patterned gecko ( Lucasium sp.) consists of dome shaped scales arranged in a hexagonal patterning. The scales comprise of spinules (hairs), from several hundred nanometres to several microns in length, with a sub-micron spacing and a small radius of curvature typically from 10 to 20 nm. This micro and nano structure of the skin exhibited ultralow adhesion with contaminating particles. The topography also provides a superhydrophobic, anti-wetting barrier which can self clean by the action of low velocity rolling or impacting droplets of various size ranges from microns to several millimetres. Water droplets which are sufficiently small (10–100 μm) can easily access valleys between the scales for efficient self-cleaning and due to their dimensions can self-propel off the surface enhancing their mobility and cleaning effect. In addition, we demonstrate that the gecko skin has an antibacterial action where Gram-negative bacteria ( Porphyromonas gingivalis ) are killed when exposed to the surface however eukaryotic cell compatibility (with human stem cells) is demonstrated. The multifunctional features of the gecko skin provide a potential natural template for man-made applications where specific control of liquid, solid and biological contacts is required.